2017
DOI: 10.3389/fphys.2017.00510
|View full text |Cite
|
Sign up to set email alerts
|

Fentanyl Promotes Breast Cancer Cell Stemness and Epithelial-Mesenchymal Transition by Upregulating α1, 6-Fucosylation via Wnt/β-Catenin Signaling Pathway

Abstract: Cancer pain is a common and severe complication of human breast cancer, and relieving pain is fundamental strategy in the treatment. Fentanyl, as an opioid analgesic, is widely used in breast cancer patients. However, little is known about its effects on stemness and epithelial-mesenchymal transition (EMT) of breast cancer cells. Aberrant protein glycosylation is involved in cancer malignancy. The α1, 6-fucosylation is an important type of glycosylation, and the elevated α1, 6-fucosylation catalyzed by fucosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 44 publications
(46 reference statements)
2
43
0
Order By: Relevance
“…Agrawal et al reveal that FUT8 mediates core fucosylation and alters L1CAM proteolytic cleavage and invasion of melanoma cells [14]. In breast cancer, the upregulation of FUT8 and α1, 6-fucosylation induce stemness and EMT by activating Wnt/β-catenin signaling pathway [15]. Our previous study indicates that FUT8 expression is signi cantly up-regulate in high metastatic hepatocellular carcinoma cells and tumor tissues [16].…”
Section: Introductionmentioning
confidence: 81%
“…Agrawal et al reveal that FUT8 mediates core fucosylation and alters L1CAM proteolytic cleavage and invasion of melanoma cells [14]. In breast cancer, the upregulation of FUT8 and α1, 6-fucosylation induce stemness and EMT by activating Wnt/β-catenin signaling pathway [15]. Our previous study indicates that FUT8 expression is signi cantly up-regulate in high metastatic hepatocellular carcinoma cells and tumor tissues [16].…”
Section: Introductionmentioning
confidence: 81%
“…Recently, some researchers reported that aberrant fucosylation and FUTs played an important role in the activation of wnt/β-catenin pathway in various diseases. Yang et al suggested that FUT8 promoted breast cancer cell stemness and epithelial-mesenchymal transition by activating wnt/β-catenin pathway 36 . Zhang et al 37 demonstrated FUT4 promoted embryo adhesion and implantation via wnt/β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, lectins have been considered as an extremely useful tool for glycomic and glycoproteomic study that can be used alone or in conjunction with other methods such as MS and CE because of the wide availability, affinity and relative specificity [93]. Several approaches based on lectins including lectin blot [94,95], lectin histochemistry/cytochemisty [29,96], lectin-antibody sandwich enzyme-linked immunosorbent assay (ELISA) [33,44,97], lectin affinity chromatography [98,99], lectin microarray [100][101][102] and lectin microfluidics [103] have been applied to capture the specific glycan of the glycoproteins [102,[104][105][106], enhancing the understanding of aberrant glycosylation and carcinogenesis, accelerating biomarkers recognition and quantitative detection. The Gao group has investigated the diagnostic and prognostic value of fucosylated fetuin A in HCC patients by AAL-based ELISA [107].…”
Section: Lectin-based Technologiesmentioning
confidence: 99%